Plasticity in bilateral hippocampi after a 3‐month physical activity programme in lung cancer patients. (30th December 2020) - Vaquero, Lucía; Rodríguez‐Fornells, Antoni; Pera‐Jambrina, María Ángeles; Bruna, Jordi; Simó, Marta
Abstract: Background and purpose: Cancer treatments have deleterious effects on both brain structure and the cognition of lung cancer patients. Physical activity (PA) has beneficial effects on the cognition of healthy adults by eliciting brain plasticity, especially on the medial temporal lobe (hippocampus). Therefore, the aim was to study the neuroprotective effects of a 3‐month PA programme (PAP) on the brain structure and cognitive performance of lung cancer patients. Methods: Twelve patients (seven non‐small‐cell lung cancer [NSCLC] patients following chemotherapy, five small‐cell lung cancer [SCLC] patients following chemotherapy and prophylactic cranial irradiation) agreed to complete the PAP and underwent baseline and 3‐month (post‐PAP) brain magnetic resonance imaging and neuropsychological evaluations (PAP group). Twelve lung cancer patients (seven NSCLC, five SCLC; non‐PAP group) and 12 healthy sex‐, age‐ and education‐matched controls were recruited and completed two evaluations separated by the same amount of time. A region of interest voxel‐based morphometry analysis focused on bilateral hippocampi was performed. Results: Physical activity programme patients presented greater grey matter volume (GMV) across time in both hippocampi. Moreover, it was observed that SCLC patients in both the PAP and non‐PAP groups presented a time‐dependent GMV loss in bilateral hippocampi that was not significant in NSCLC patients. Importantly, the PA intervention decreased the magnitude of that GMV loss, becoming thus especially beneficial at the brain structural level for SCLC patients. Conclusions: Our study demonstrates, using a neuroimaging approach for the first time, that PA is able to stop the deleterious effects of systemic chemotherapy and brain radiation on brain structures of the lung cancer population, especially in SCLC patients. Abstract : Neuroprotective effects of a 3‐month physical activity (PA) programme on brain structure and cognitive performance of lung cancer patients were explored. Small‐cell lung cancer (SCLC) patients, who underwent systemic chemotherapy and prophylactic cranial irradiation, showed a time‐dependent loss in grey matter volume (GMV) in bilateral hippocampi. The PA intervention decreased the magnitude of that GMV loss, which suggests that PA could be a clinically relevant approach to overcome the deleterious effects of systemic chemotherapy and brain radiation in the lung cancer population (especially SCLC). Future studies with bigger samples are needed to confirm these findings and potentially find behavioural correlates.